Extramedullary Pulmonary Manifestations of Relapsed/Refractory Multiple Myeloma: A Case Series and Brief Review of the Literature - Sagar Kumar; Anita Mazloom; Marialaina Carter; FNU Manisha; Jacek Polski; Omar Alkharabsheh (MDPI AG, 2024)
Extramedullary myeloma with pulmonary and pleural involvement is rare and can present in different ways. Here we present two cases of extramedullary pulmonary disease in relapsed/refractory multiple myeloma. Background: Multiple myeloma remains an incurable disease with unmet need for new treatments for high-risk disease such as extramedullary plasmacytoma. Relapses can occur at different stages due to the heterogeneity of the disease. While relapsed/refractory disease can be challenging to treat, progression can also lead to extramedullary disease which indicates an aggressive form with poor outcomes. Pulmonary extramedullary disease can present in various ways, such as a lung mass, parenchymal infiltrates, pleural mass, or pleural effusion. Objective: Our case series highlights two different presentations of pulmonary extramedullary disease and a review of the treatment of relapsed/refractory myeloma. Our patients highlight the progression of their multiple myeloma due to the aggressive nature of their extramedullary disease. Their cases emphasize the importance of new targeted treatments to treat extramedullary disease and penta-refractory disease as there is no currently accepted standard regimen for this difficult to treat condition.